Development of perovskite-based light emitting diodes with improved stability 2.0 - Teo, Zan Wei Jie (2019)
Due to their remarkable photophysical properties, perovskite semiconductors gained massive attention in recent years. All-inorganic and Hybrid perovskites were both testified to possess outstanding optical properties, where all-inorganic perovskites performed better in terms of stability by resisting adverse conditions like heat, water and Ultraviolet (UV) light exposure. Therefore, the development of all-inorganic perovskites gained attention in the research field. CsPbX3 perovskites is a type of inorganic perovskites which have been prepared using several ways like microwave irradiation, hot-injection, solvothermal and room-temperature methods. However, improvement could be made in terms of the stability of the perovskite-based light emitting diodes for further real-world applications. Through the usage of high binding ability ligands, the stability of CsPbX3 perovskite nanocrystals (NCs) improved and generated high photoluminescence quantum yields (PLQYs) as well as the ligand coverage(surface) of ligands is expected to expand remarkably. The use of Stearic Acid enhanced the chemical stability and PLQY of the CsPbX3 perovskite NCs tremendously. The presence of SA lengthened the distance between perovskite NCs that restrict the close contact and diminish the possibility of regrowth, which plays a crucial role to sustain the significant PLQY as well as enhance the NCs’ stability. The difference proved that the usage of SA(ligand) manages to restrict the agglomerate of NCs, hence refrain from the regrowth induced instability. Interligand interaction is a crucial factor that tremendously affects the binding ability of the ligands, therefore, to increase the binding ability, strong interligand interaction is essential. Thus, different ligands’ types can affect the PLQYs of perovskite NCs.